PREPARATION AND CHARACTERIZATION OF GLIADIN NANOPARTICLES FOR BRAIN DRUG DELIVERY - Dubey, Ankit Dubey Naveneet; Ramteke, Suman; Jain, Deepti (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: The aim of the present work is to prepare and evaluate nasal controlled release gliadin nanoparticles of sumatriptan for antimigraine activity to improve patients’ compliance by simplifying its administration, improving its therapeutic effect, and reducing its dose-related side effects through brain targeting. Methods: Sumatriptan containing gliadin nanoparticles were prepared by desolvation method using Pluronic F-68 as a stabilizing agent. Results: The results show that this method is reproducible very easy and led to the efficient entrapment of drug as well as the formation of spherical particles ranging from 1 to 181 nm, respectively. The controlled release behavior of gliadin nanoparticles was evaluated both in phosphate buffer saline 7.4 pH and in phosphate buffer 6.8 pH, respectively, at 37Â±1Â°C. Their brain targeting properties were determined by the nasal route through in vitro and in vivo methods. Conclusion: The optimized nanoparticles showed higher release rate than other marketed formulation like a tablet, nasal spray this may be due to nano size of the particles, glutaraldehyde was added to this system that increased hardness and F-68 increased the stability of nanoparticles .tablet, nasal spray this may be due to nano size of the particles, glutaraldehyde was added to this system that increased hardness and F-68 increased the stability of nanoparticles. The in vivo results showed that within 15 min maximum concentration of sumatriptan was observed in brain as compare to plasma which could be due to small particle size and lipophilic nature of gliadin nanoparticles.Â